ANTESEDEN KEPUTUSAN PENGGUNAAN E-WALLET DANA: STUDI PADA MAHASISWA MANAJEMEN FEB UNRAM: Antecedents Of The Decision To Use Dana E-Wallet: A Study Of Management Students Of Feb Unram - Pradnyani, I Gusti Agung Arista; Atmaja, I Gusti Putu Widya; Rahayu, Nila; Maryanti, Sri (Ganec Swara, 2025)
This study aims to examine the influence of Digital Marketing, Word of Mouth, Brand Trust, and Digital Financial Literacy on the decision to use the DANA e-wallet among Management students at the Faculty of Economics and Business, University of Mataram. The research employs an associative quantitative approach with a sample of 84 respondents selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression with SPSS software. The results indicate that Digital Marketing, Brand Trust, and Digital Financial Literacy significantly affect the decision to use the DANA e-wallet. Digital Marketing and Brand Trust have positive effects, while Digital Financial Literacy shows a significant negative effect, suggesting that users with higher literacy tend to be more selective in using the application. Meanwhile, Word of Mouth has no significant impact on the usage decision. This study recommends that e-wallet managers enhance educational digital marketing strategies and build consumer trust, while also addressing digital financial literacy aspects to support prudent usage decisions.